Translation and validation study of the Polish version of the Brief Hepatitis C Knowledge Scale - Tronina, Olga (PLoS One, 2020)
INTRODUCTION: Chronic hepatitis C (HCV), considered by the World Health Organization as one of the greatest epidemiological health hazards, often with asymptomatic clinical course and one which, due to scanty knowledge, remains a crucial risk factor of serious chronic HCV infection complications. The purpose of this study is to validate the psychometric properties of the Polish version of the validated Brief Hepatitis C Knowledge Scale (BHCKS_PL), developed by Balfour in 2009. METHODS: The study, conducted from May to July 2018, included 246 persons (68,69% females), divided into four subgroups: patients (n = 86), nursing students (n = 74), medical students (n = 28), healthcare workers (nurses and doctors; n = 58). The 19-items questionnaire contained questions designed to assess general knowledge regarding hepatitis C and the transmission risk factors. RESULTS: An evaluation by means of multiple comparisons in pairs showed that there were significant differences in the knowledge level between the group of patients and the group of nursing students (Mdn: 14.0 vs 11.0, z = 7.713, P<0.001), and between students of medicine (Mdn: 16.0 vs 11.0, z = 0.339, P<0.001) and healthcare workers (17.0 vs 11.0, z = 11.447, P<0.001). Moreover, significant differences were observed between the groups of students of nursing and medicine (Mdn: 14.0 vs 16.0, z = 3.646, P = 0.002) and healthcare workers (Mdn: 14.0 vs 17.0, z = 4.117, P<0.001). No significant differences in the knowledge level between the students of medicine and healthcare workers were observed (z = 0.377, P = 1.000). CONCLUSIONS: The completed validation suggests good BHCKS_P psychometric characteristics with the internal consistency convergent and known-groups validity. The questionnaire can be used in educational practice. The obtained results of the measurement provide information about the studied person based on the total score.